Students Mental Readiness for Entrepreneurship at SMK Negeri 6 Padang - Pertiwi, Ayunda; Yulastri, Asmar; Gusnita, Wiwik; Siregar, Juliana (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by the large number of students at SMK Negeri 6 Padang who graduated but faced difficulties in finding work or were even unemployed. This is due to a lack of desire to start a business. Students feel less confident in starting a business. The aim of this research is to describe the mental readiness of students for entrepreneurship at SMK Negeri 6 Padang. This type of research is quantitative with a descriptive approach. The population in this study were students at SMK Negeri 6 Padang, totaling 303 students. The sample consisted of 75 students. Sampling used the Proportional Random Sampling technique. The data collection technique uses questionnaires via Google Form which have been tested for validity and reliability. The data analysis technique was carried out using descriptive analysis. Data processing was carried out with the help of Microsoft Excel and the SPSS version 25 software program. First determine the frequency distribution, determine the percentage level and classification techniques. The research results showed that 26 students' mental readiness for entrepreneurship (35%) was in the medium category.